2018
DOI: 10.31062/agrom.v25i2.24834
|View full text |Cite
|
Sign up to set email alerts
|

Sowing times influence canola grain yield and oil quality

Abstract: The aim of this study was to evaluate the environmental effect of different sowing times on the productivity and quality of hybrid canola grains Hyola 60, Hyola 61, Hyola 401 and Hyola 432 sown on the dates 05/12/08, 05/31/08, 06/21/08 and 08/02/08, with a sowing test on 04/18/08 with Hyola 401 and Hyola 61 hybrids. The experimental design consisted of randomized blocks in a factorial 4 dates x 4 hybrids. The local environment was characterized by air temperature, relative humidity and rainfall. With these dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…For example, early seeding can improve canola emergence, reduce the risk of heat stress during flowering and seed filling, and increase the oil content and fatty acid composition and yield of canola grains [93,94]. In a study conducted by Righi et al [95] in Brazil, there was a trend of reduction in grain productivity and quality with delayed sowing in four hybrids of canola sown on different dates. The authors found that one hybrid had better productivity and presented the best quality indicators such as oil content, protein content, chlorophyll content, GSL content, and fatty acid composition.…”
Section: Agronomic Practices and Management Techniquesmentioning
confidence: 99%
“…For example, early seeding can improve canola emergence, reduce the risk of heat stress during flowering and seed filling, and increase the oil content and fatty acid composition and yield of canola grains [93,94]. In a study conducted by Righi et al [95] in Brazil, there was a trend of reduction in grain productivity and quality with delayed sowing in four hybrids of canola sown on different dates. The authors found that one hybrid had better productivity and presented the best quality indicators such as oil content, protein content, chlorophyll content, GSL content, and fatty acid composition.…”
Section: Agronomic Practices and Management Techniquesmentioning
confidence: 99%